A pragmatic approach towards end-user engagement in the context of peer-to-peer energy sharing. (15th August 2020) - Klein, Lurian P.; Matos, Luisa M.; Allegretti, Giovanni
Abstract: Peer-to-peer (P2P) energy sharing is a fast-emerging concept that concerns electricity exchanges between grid-connected end-users. This innovative user-centric market model incentivises the creation of more distributed, collaborative, and democratised energy networks compared to traditional ones. Current research on P2P energy sharing has essentially focused on the definition of its techno-economic attributes, hence sound research on end-user engagement in this context is still lacking in the scientific literature. This paper addresses this knowledge gap by proposing a novel end-user engagement framework constructed around the P2P energy sharing context that was trialled in 3 different pilots in Portugal. These pilots represent the first Portuguese testing grounds where this concept was demonstrated under real market conditions. Findings based on a sample of 123 participants suggest that the proposed framework was effective in raising awareness and empowering unmotivated, passive end-users in an initial phase of the project implementation, as well as in retaining the interest of motivated end-users during a later phase. Furthermore, the empirical analysis allowed to conclude that participation in the project was predominantly voluntary rather than coerced. The proposed end-user engagement framework contributes to the scientific literature since it facilitates and guides the design of future P2P energy sharing initiatives. Highlights: The first end-user engagement framework framed on P2P energy sharing is presented. The impact of the framework on 123 participants from 3 real-life pilots is assessed. The framework was effective in raising awareness in the initial phase of the project. The framework retained the interest of end-users in a later phase of the project. Participation in the project was predominantly voluntary rather than coerced.